Synthesis of a Water-Soluble Ruthenium Complex and Its Catalytic Activity for Acceptorless Alcohol Dehydrogenation in Aqueous Medium - Bhatia, Anita; Muthaiah, Senthilkumar (Synlett, 2018)
The synthesis of a ruthenium complex bearing a PN-chelating ligand is described. The complex, in the presence of KOH, enabled the synthesis of ketones from secondary alcohols in the absence of a hydrogen acceptor in aqueous medium. This synthetic protocol, which uses water as the medium, is green and has a high atom economy as it avoids the use of an acceptor and produces hydrogen as the sole byproduct. Mechanistic investigations revealed that the catalytic cycle involves a phosphine dissociative pathway.
Keywords: alcohols; ketones; ruthenium catalysis; ligands; dehydrogenation